Cleaning Efficiency of Root Canal after Irrigation with New Irrigation Technique: A Scanning Electron Microscopic Study - Shalan, Linz Ali; Al-huwaizi, Hussain F. (Iranian Endodontic Journal, 2019)
Introduction: The aim of this study was to evaluate the ability of pressurized water irrigation technique (AquaPick Device) as an intra-canal irrigation technique and compare it with sonic irrigation device (Endoactivator) for their ability to remove smear layer from canals. Methods and Materials: Total number of 80 single rooted teeth (premolars) were prepared, divided into eight main groups, Group 1: Aquapick with apically vented needle/18 mm depth, Group 2: Aquapick with apically vented needle/15 mm depth, Group 3: Endoactivator device/18 mm depth, Group 4: Endoactivator device/15 mm depth, Group5: Aquapick with 2 side vented needle/18 mm depth, Group 6: Aquapick with 2 side vented needle/15 mm depth and two control groups. Then all samples were tested by SEM in 3, 6 and 9-mm distances from the apical foramen. The data were statistically analyzed using Kruskal Wallis and Mann-Whitney U tests. Results: There was a high significant difference among the tested groups with the best removal of smear layer by the use of pressurized water irrigation device with apical vented needle especially at the 3 mm area. Conclusion: Pressurized water irrigation technique could be used as intra-canal irrigation technique with good results. Keywords: AquaPick Device; Endoactivator; Smear Layer Removal; Pressurized Water